The Removal of Metallic Single-Walled Carbon Nanotubes Using an Aqueous Two-Phase System - Tang, M.S.Y.; Whitcher, T.J.; Yeoh, K.H.; Chua, C.L.; Woon, K.L.; Show, P.L.; Lin, Y.K.; Ling, T.C. (American Scientific Publishers, 2014)
Here we report our findings on the removal of metallic single-walled carbon nanotubes using an aqueous two-phase system. The aqueous two-phase system contained as received carbon nanotubes, polyethylene glycol, dextran, N-methylpyrrolidone, cetyltrimethylammonium bromide, and water which phase separated into top and bottom phases. The top phase was dominated by polyethylene glycol whereas the bottom phase was dominated by dextran. The dextran-rich phase contained more semiconducting species while metallic species was more abundant in the polyethylene glycol rich-phase. It was found via Fourier-Transform Infrared Spectroscopy that cetyltrimethylammonium bromide only present in the dextran-rich phase. A selectivity mechanism is tentatively proposed and discussed.